Hematopoietic cell activation in the subventricular zone after Theiler's virus infection. - Goings, G; Greisman, A; James, R; Abram, L; Begolka, W; Miller, S; Szele, F (2008)
BACKGROUND: The periventricular subventricular zone (SVZ) contains stem cells and is an area of active neurogenesis and migration. Since inflammation can reduce neurogenesis, we tested whether Theiler's murine encephalomyelitis virus (TMEV) induces inflammation and reduces neurogenesis in the SVZ. METHODS: We performed immmunohistochemistry for the hematopoietic cell marker CD45 throughout the central nervous system and then examined neuroblasts in the SVZ. RESULTS: CD45+ activation (inflammation) occurred early in the forebrain and preceded cerebellar and spinal cord inflammation. Inflammation in the brain was regionally stochastic except for the SVZ and surrounding periventricular regions where it was remarkably pronounced and consistent. In preclinical mice, SVZ neuroblasts emigrated into inflamed periventricular regions. The number of proliferating phoshpohistone3+ cells and Doublecortin+ (Dcx) SVZ neuroblasts was overall unaffected during the periods of greatest inflammation. However the number of Dcx+ and polysialylated neural cell adhesion molecule (PSA-NCAM+) SVZ neuroblasts decreased only after periventricular inflammation abated. CONCLUSION: Our results suggest that after TMEV infection, the SVZ may mount an attempt at neuronal repair via emigration, a process dampened by decreases in neuroblast numbers.